The Influence of Organizational Culture on Increasing Employee Motivation in Sumut Bank of Sharia Unit, North Sumatera - Nur M Ridha Tarigan; Supar Wasesa (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
This study wants to describe the influence of organizational culture on increasing employee motivation in Sumut Bank of sharia unit, North Sumatera. This research uses descriptive and verification methods. The place of research was conducted at Sumut Bank of Sharia Unit in North Sumatera. Considering the nature of this research is descriptive and verification, the research method used is descriptive survey and explanatory survey method. The type of investigation in this research is causality, which is testing the causal relationship between independent variables, intervening variables, moderating variables and dependent variables. The unit of analysis in this study is the employees at the North Sumatra Syariah Unit Bank in North Sumatra. The result shows that Organizational Culture on Increasing Employee Motivation in Sumut Bank of Sharia Unit, North Sumaterais perceived as less powerful to very strong. The highest average value on management indicators supports strengthening organizational culture, meaning that management always improves organizational culture as a support of the company's goals.